Hydroxynorketamine, but not ketamine, acts via α7 nicotinic acetylcholine receptor to control presynaptic function and gene expression - Debarpan Guhathakurta; Aneta Petrušková; Enes Yağız Akdaş; Bartomeu Perelló-Amorós; Renato Frischknecht; Daniela Anni; Eva-Maria Weiss; Martin Walter; Anna Fejtová (Translational Psychiatry, 2024)
Abstract Ketamine is clinically used fast-acting antidepressant. Its metabolite hydroxynorketamine (HNK) shows a robust antidepressant effect in animal studies. It is unclear, how these chemically distinct compounds converge on similar neuronal effects. While KET acts mostly as N-methyl-d-aspartate receptor (NMDAR) antagonist, the molecular target of HNK remains enigmatic. Here, we show that KET and HNK converge on rapid inhibition of glutamate release by reducing the release competence of synaptic vesicles and induce nuclear translocation of pCREB that controls expression of neuroplasticity genes connected to KET- and HNK-mediated antidepressant action. Ro25-6981, a selective antagonist of GluN2B, mimics effect of KET indicating that GluN2B-containing NMDAR might mediate the presynaptic effect of KET. Selective antagonist of α7 nicotinic acetylcholine receptors (α7nAChRs) or genetic deletion of Chrna7, its pore-forming subunit, fully abolishes HNK-induced synaptic and nuclear regulations, but leaves KET-dependent cellular effects unaffected. Thus, KET or HNK-induced modulation of synaptic transmission and nuclear translocation of pCREB can be mediated by selective signaling via NMDAR or α7nAChRs, respectively. Due to the rapid metabolism of KET to HNK, it is conceivable that subsequent modulation of glutamatergic and cholinergic neurotransmission affects circuits in a cell-type-specific manner and contributes to the therapeutic potency of KET. This finding promotes further exploration of new combined medications for mood disorders.